Governing aboriginal justice in Canada: constructing responsible individuals and communities through ‘tradition’ - Andersen, Chris (Crime, law and social change, 1999)
In recent years, Aboriginal justice projects have gained in popularity in such places as Australia, New Zealand, the United States, and Canada. However, these programs have remained relatively insulated from external critique, particularly as it relates to the problem of grafting "traditional" principles onto non-traditional forms of social organization. The purpose of this paper is to discuss this shortcoming in the context of examining the relationship between newly emerging neo-liberal discourses about personal responsibility and the function of "community" as a domain of freedom, in Aboriginal restorative justice programs in Canada.